Is There a Gap Among Gender in Vocational Training Incidence in Labour Market in Albania? - Alikaj, Lorena; Guga, Klaudja (European Scientific Journal, ESJ, 2017)
Human capital theory states that the incidence of training should be higher among men than women. Literature have confirmed it in different empirical studies. Recently, there is a small number of studies that have reported the reversed trend: women are now more likely to participate in training than their male counterparts. Using Labour Force Survey data we present a descpritive analysis to evaluate if there are evidences of discrimination; if it’s measurable and which are the determinants of vocational training of men and women employees in the Albanian labor market. Determinants such as improvements in the labour market status of women (Vanden Heuvel, 1997) increased labour force participation rates among women (Green and Zanchi, 1997) are detected in the paper. This paper should be seen as a actual scan of Albanian labour market in context of vocational training incidence and evidences of discrimination among gender.